The Bacterial Flora of the Upper Respiratory Tract in Budgerigars and Peaceful Doves in Captivity - Liau, Chai Bong (1997)
A bacteriological investigation of the upper respiratory tract of clinically healthy and sick budgerigars and peaceful doves from five pet shops within the Klang Valley as well as the antibiotic sensitivity tests of potentially pathogenic microorganisms isolated from the sick bird samples were reported. In the healthy budgerigar group, gram-positive microorganisms were more commonly isolated (80%) than gram-negative microorganisms (20%). In the sick budgerigar group, isolation of gram-negative microorganisms mainly E. coli was increased to 41% as compared to 20% in healthy budgerigars. In the healthy and sick dove groups, about 50% of gram-negative microorganisms were isolated in each group. Mycoplasma gallinarum and other untyped Mycoplama spp. were found mainly in the doves in both the healthy and sick groups with almost similar number of microorganisms. Antibiotic sensitivity tests revealed that most gram-negative microorganisms tested were sensitive to enrofloxacin, polymycin B and newer third generation of aminoglycosides such as amikacin and gentamicin.